The effect of weld groove variations on the toughness of welding joints of AISI 1050 material - Zulkiffli Purba; Samsul Bahri; Jenne Syarif (Politeknik Negeri Lhokseumawe, 2022)
SMAW (Shielded Metal Arc Welding) welding is a metal joining process that uses heat energy to melt the workpiece and electrode (fill material). The flux material used for type E7016, a low hydrogen electrode wire typically used for welding heavy-duty plates and structures. Its use is for welding medium carbon steel, bridges, ships and machinery. The result of welding electrode E7016 is very smooth, deep penetration, crack resistant, ductile, good weld appearance and stable arc, the material used in the SMAW welding process is AISI 1050 steel. While AISI 1050 steel is steel that has a carbon content of 0.50 % so that it is classified as medium carbon steel. This steel is widely used in the market because it has many advantages, one of which is as an automotive component. This steel has the characteristics of good machinability, good wear resistance and medium mechanical properties. This study aims to determine the shock strength (impact) and the difference in the time of making weld grooves on SMAW welding results on AISI 1050 steel with variations of Double Bevel and Double V Groove grooves. In testing in the Weld Metal area with a current used of 110 Ampere. From the tests that have been carried out, it is known that the value of the highest impact strength is in the Double Bevel groove which has a value of 1.91 Joule/mm2, for the manufacture of welded grooves where the Double Bevel time is shorter than Double V Groove, so the time produced by Double Bevel which is 3.44 minutes/second.